2001
DOI: 10.1007/s004390100553
|View full text |Cite
|
Sign up to set email alerts
|

A polymorphism in the promoter region of catalase is associated with blood pressure levels

Abstract: Catalase is an important antioxidant enzyme that detoxifies H2O2 into oxygen and water and thus limits the deleterious effects of reactive oxygen species (ROS). Because chronic exposure to excess ROS may contribute to vascular damage, we investigated whether genetic variation in catalase was associated with susceptibility to essential hypertension (EHYT) in 324 individuals (at least 50 years old) who were randomly sampled from an isolated population living in Xiangchang, China. They were screened for genetic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 19 publications
3
51
0
3
Order By: Relevance
“…Although smoking did not seem to affect associations, there was modification of relationships by consumption of fruits and vegetables, with catalase activity decreasing with increasing intake, only among those with CT or TT genotypes. These findings support our a priori hypothesis that CT and TT genotypes are associated with lower catalase activity and provide a biological basis for epidemiologic studies showing associations between CAT genotype and risk of diseases related to oxidative stress (13,14,16,20).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Although smoking did not seem to affect associations, there was modification of relationships by consumption of fruits and vegetables, with catalase activity decreasing with increasing intake, only among those with CT or TT genotypes. These findings support our a priori hypothesis that CT and TT genotypes are associated with lower catalase activity and provide a biological basis for epidemiologic studies showing associations between CAT genotype and risk of diseases related to oxidative stress (13,14,16,20).…”
Section: Discussionsupporting
confidence: 86%
“…with CC genotype, and those with CT genotype had intermediate risk (13). Thus, our findings of genotype/ phenotype relationships support the results from epidemiologic studies, providing a functional basis for the investigation of the À262C !…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consistent with this hypothesis, our results demonstrated that the risk of spontaneous abortion had increased in women with C/C genotype. Reduced risk of the T allele has also been reported in patients with type 1 diabetes [Chistiakov et al 2004], hypertension [Jiang et al 2001], and breast cancer [Ambrosone et al 2005]. Overdominant selection favoring heterozygotes and associative overdominance can lead to excess of heterozygote observed in the results.…”
Section: Resultsmentioning
confidence: 95%
“…25 CAT is an important antioxidant enzyme that detoxifies H 2 O 2 into oxygen and water, and thus limits the deleterious effects of reactive oxygen species (ROS). 15 CAT regulates plasma levels of ROS and together with nitric oxide (NO), influences angiotensin-converting enzyme (ACE) activation, LDL oxidation, adhesion molecule expression, platelet aggregation, endothelial cell apoptosis and vascular smooth cell growth. Most previous studies only considered single-gene effects, although hypertension is a complex multi-factorial and polygenic disorder.…”
Section: Discussionmentioning
confidence: 99%